My Phone Lies to Me Fake News Poetry Workshops As Radical Digital Media Literacy Given the Fact of Fake News - Juhasz, Alexandra (punctum books, 2022)
This book of poems about fake news written by diverse project participants is foremost an invitation and invocation for readers to participate, with others, in an experiment in knowing and working differently with the internet: Fake News Poetry Workshops. Between 2018 and 2020, Alexandra Juhasz directed more than twenty of these workshops around the world, and these are ongoing beyond the confines of this book. Each differs in form and structure, but participants are always asked to attend to research, their own knowledge about the internet and social media, and what they can learn from their workshop and previous ones. My Phone Lies to Me shares the poems created in the workshops. As moving, eloquent, and useful as they may be - and you are invited to indulge in and learn from them - enjoying and learning from the poems is only a small part of this book's project. Four short essays (two by Juhasz, with a foreword and afterword by critical internet scholars Tara McPherson and Margaret Rhee, respectively) introduce and situate the project's processes of radical digital media. You can learn what Fake News Poetry Workshops make, do, and believe in, as well as how to collaborate with others to create your own. Fake News Poetry Workshops are one way to counter dominant and dominating internet modes and values, to fight the corrupt ways of being and knowing that use digital media to create, fuel, and weaponize fake news. The project verifies good news in the face of fake news: that we can gather together in our many local places and use analog structures (about digital things and ways) to generate, hold, and share ""art answers to phony questions.